Analisis Kurikulum Merdeka Mengenai Sikap dan Nilai Siswa pada Kelas Menengah Pertama - Widiyantoro Widiyantoro (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
This study aims to analyze the implementation of the Kurikulum Merdeka (Freedom Curriculum) in developing students' attitudes and values at the junior high school level. The Kurikulum Merdeka, which focuses on student-centered and project-based learning, provides teachers with flexibility to integrate Pancasila values, such as mutual cooperation, justice, and tolerance, into learning activities. The findings indicate that this approach positively impacts students' curiosity, creativity, responsibility, as well as critical thinking and collaboration skills. Teachers play a crucial role as facilitators and role models, creating an inclusive and relevant learning environment tailored to students' needs. However, the implementation of the Kurikulum Merdeka faces challenges, including the readiness of human resources and infrastructure support. This study concludes that the Kurikulum Merdeka holds significant potential to shape students with strong character and global relevance, provided it is supported by collaboration among teachers, families, and communities.